(untitled) (Research, Society and Development, 2021)
According to the Brazilian Institute of Geography and Statistics (IBGE), Brazil has more than 240 indigenous communities. The ethnographic characteristics of these communities corroborated for a wide variety of determinants of the health-disease process, where the effectiveness of basic health care actions is a challenging mission. This work is an integrative review, which aimed to analyze studies on the oral health conditions of Brazilian indigenous peoples, their objectives and results. The articles compiled in this study were selected through the databases: PubMed, Lilacs and Scielo. The survey was limited to articles published in English and Portuguese, between 2000 and 2020, using the standardized descriptors: Oral Health; Indigenous Health; South American Indians and their English counterparts, the Boolean operator And was used in all combinations. In order to be included in the analysis, the following criteria were used: be in article format, have title and abstract that are similar to the objectives of the work and be published in full. It was observed that due to socio-demographic peculiarities, many of these have been restricted to the benefits of routine dental care programs, resulting in an insipient control of caries and the development of various oral diseases. However, it was evident that the oral health condition of Brazilian indigenous peoples is precarious and that this condition of degradation can only be resolved through more comprehensive epidemiological studies, in addition to the implementation of preventive and oral health promotion actions.